Miniature Crowd Frescoes from Knossos: A Topography of the World Seen - Valentinová, Lucie (My University, 2022)
This study discusses prevailing interpretations of the miniature frescoes from Knossos as depictions of some sort of ritual or ceremony, located topographically in Knossos’s Central and West Courts. It revises the question of the narrativity of Minoan frescoes, based on the interpretive approach developed by Alpers in her exploration of seventeenth-century Dutch art and ‘visual culture’. Applying Alpers’s insights for Minoan frescoes allows for an original interpretation based on a formal analysis of their non-narrative devices of representation, namely (1) vertical perspective, (2) map-like composition and (3) suppressed focalisation. The study demonstrates that once their representational strategy is recognised as non-narrative, it is no longer possible to interpret the subject theme of the Knossian miniatures by applying the frequently used narrative analytical category of ritual as a transformative ‘event’. Instead, the operation of these devices focuses our attention on the performative dimension of viewing as testifying to the knowledge of the land and society and the specific way in which the Knossian miniature frescoes absorb their viewer into this performance.
Miniaturní fresky z Knóssu: Topografie viděného světa
Keywords: Svetlana Alpers; map-like composition; Minoan miniature frescoes; ritual theory; suppressed focalisation; vertical perspective; Svetlana Alpers; Mínójské miniaturní fresky; kompozice podobná mapě; teorie rituálu; potlačená fokalizace; vertikální perspektiva